2013
DOI: 10.1371/journal.ppat.1003705
|View full text |Cite
|
Sign up to set email alerts
|

O-mannosylation of the Mycobacterium tuberculosis Adhesin Apa Is Crucial for T Cell Antigenicity during Infection but Is Expendable for Protection

Abstract: Glycosylation is the most abundant post-translational polypeptide chain modification in nature. Although carbohydrate modification of protein antigens from many microbial pathogens constitutes important components of B cell epitopes, the role in T cell immunity is not completely understood. Here, using ELISPOT and polychromatic flow cytometry, we show that O-mannosylation of the adhesin, Apa, of Mycobacterium tuberculosis (Mtb) is crucial for its T cell antigenicity in humans and mice after infection. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 56 publications
2
48
0
Order By: Relevance
“…at week 52 or thereafter. This viewpoint is further supported by a recent data from our laboratory, where boosting with Apa (Rv1860)-based subunit vaccine during the contraction phase offered a stronger boost and imparted significant protection [80]. The data also reinforces the fact that in most published vaccine studies, mice are challenged far too quickly [9] and the longer vaccination-to-challenge intervals, such as 6–8 months after BCG vaccination, will provide better information about the protective efficacy of preclinical vaccines against Mtb infection in the mouse model.…”
Section: Discussionsupporting
confidence: 61%
“…at week 52 or thereafter. This viewpoint is further supported by a recent data from our laboratory, where boosting with Apa (Rv1860)-based subunit vaccine during the contraction phase offered a stronger boost and imparted significant protection [80]. The data also reinforces the fact that in most published vaccine studies, mice are challenged far too quickly [9] and the longer vaccination-to-challenge intervals, such as 6–8 months after BCG vaccination, will provide better information about the protective efficacy of preclinical vaccines against Mtb infection in the mouse model.…”
Section: Discussionsupporting
confidence: 61%
“…The secreted antigen is not present in other mycobacterial species, including M. avium, M. marinum or M. smegmatis (Ragas et al, 2007;Nandakumar et al, 2013). Apa is targeted by, and binds directly to, the human PSP-A, an innate immune system C-type lectin responsible for early recognition of invading pathogens (Ragas et al, 2007).…”
Section: Tuberculosis Pilimentioning
confidence: 99%
“…Apa has been proposed as a possible vaccine candidate or component for future vaccines against TB. Nandakumar et al (2013) showed that Apa offered significant protection against virulent M. tuberculosis in mice when used as a BCG-booster vaccine.…”
Section: Tuberculosis Pilimentioning
confidence: 99%
“…Interestingly, the MS analyses identified 13 glycoproteins in Mtb CF in contrast to the 41 captured by affinity chromatography (González-Zamorano et al, 2009; Smith et al, 2014). Liu et al (2013) first linked a functional and virulent role to the Mtb mannosyl transferase membrane protein (Rv1002c) by establishing a Δ Rv1002c mutant.…”
Section: History Of Mycobacterial Glycoproteinsmentioning
confidence: 99%